Clinical Significance of NAT2 Genetic Variations in Type II Diabetes Mellitus and Lipid Regulation - Jarrar Y; Abudahab S; Abdul-Wahab G; Zaiter D; Madani A; Abaalkhail SJ; Abulebdah D; Alhawari H; Musleh R; Lee SJ (Dove Medical Press, 2023)
Yazun Jarrar,1 Sara Abudahab,2 Ghasaq Abdul-Wahab,3 Dana Zaiter,4 Abdalla Madani,4 Sara J Abaalkhail,4 Dina Abulebdah,4 Hussam Alhawari,5 Rami Musleh,6 Su-Jun Lee7 1Department of Basic Medical Sciences, Faculty of Medicine, Al-Balqa Applied University, Al-Salt, Jordan; 2Department of Pharmacotherapy and Outcomes Science, School of Pharmacy, Virginia Commonwealth University, Richmond, VA, USA; 3Department of Oral Surgery and Periodontology, College of Dentistry, Al-Mustansiriya University, Baghdad, Iraq; 4Department of Pharmacy, Faculty of Pharmacy, Al-Zaytoonah University of Jordan, Amman, Jordan; 5Department of Internal Medicine, School of Medicine, The University of Jordan, Amman, Jordan; 6Department of Pharmacy, Faculty of Medicine and Health Sciences, An-Najah National University, Nablus, Palestine; 7Department of Pharmacology, Pharmacogenomics Research Center, College of Medicine, Inje University, Busan, KoreaCorrespondence: Yazun Jarrar, Department of Basic Medical Sciences, Faculty of Medicine, Al-Balqa Applied University, Al-Salt, 19117, Jordan, Email yazan.jarrar@bau.edu.joBackground: N-acetyltransferase 2 (NAT2) enzyme is a Phase II drug-metabolizing enzyme that metabolizes different compounds. Genetic variations in NAT2 can influence the enzyme's activity and potentially lead to the development of certain diseases.Aim: This study aimed to investigate the association of NAT2 variants with the risk of Type II diabetes mellitus (T2DM) and the lipid profile among Jordanian patients.Methods: We sequenced the whole protein-coding region in NAT2 using Sanger's method among a sample of 45 Jordanian T2DM patients and 50 control subjects. Moreover, we analyzed the lipid profiles of the patients and examined any potential associations with NAT2 variants.Results: This study revealed that the heterozygous NAT2*13 C/T genotype is significantly (P = 0.03) more common among T2DM (44%) than non-T2DM subjects (23.5%). Furthermore, the frequency of homozygous NAT2*13 T/T genotype was found to be significantly higher (P = 0.03) among T2DM patients (26.7%) compared to that of non-T2DM subjects (11%). The heterozygous NAT2*7 G/A genotype was exclusively observed in T2DM patients (11.1%) and absent in the control non-T2DM group. Moreover, among T2DM patients, those with a homozygous NAT2*11 T/T genotype exhibited significantly higher levels of triglycerides (381.50 ± 9.19 ng/dL) with a P value of 0.01 compared to those with heterozygous NAT2*11 C/T (136.23 ± 51.12 ng/dL) or wild-type NAT2*11 C/C (193.65 ± 109.89 ng/dL) genotypes. T2DM patients with homozygous NAT2*12 G/G genotype had a significantly (P = 0.04) higher triglyceride levels (275.67 ± 183.42 ng/dL) than the heterozygous NAT2*12 A/G (140.02 ± 49.53 ng/dL) and the wild NAT2*12 A/A (193.65 ± 109.89 ng/dL).Conclusion: The finding in this study suggests that the NAT2 gene is a potential biomarker for the development of T2DM and changes in triglyceride levels among Jordanians. However, it is important to note that our sample size was limited; therefore, further clinical studies with a larger cohort are necessary to validate these findings.Keywords: type II diabetes mellitus, N-acetyltransferase 2, NAT2, triglyceride, genetic variants, Jordanian population